Réponses

Meilleure réponse !
2013-05-13T22:02:36+02:00

Bonsoir

h+r =5                          et              h²- r² = 4 

h = 5 - r                       alors         ( 5 - r )² - r² = 4

                                                       25  + r² - 10r - r² = 4

                                                        -10r = 4 - 25

                                                          r = -21/10

h = 5 - (21/10)

h = (50/10) - (21/10)

h = 29/10 

2013-05-13T22:57:03+02:00
On sait que h2-r2 donc h+r= 5
H= 5 - r (5-r)2 - r 2 = 4 25 + r 2
10-r2 = 4 -10r = -21/10
H= 5- (21/10) don h = 29/10